"Unaccomodated Man": Dismodernism and Disability Justice in King Lear - Gottlieb, Christine M. (Disability Studies Quarterly, 2018)
King Lear's exploration of what it means to be human has significant Disability Studies implications that have not yet been examined. Through the course of the play, Lear gains awareness of interdependence, bodily vulnerability, and human-animal kinship, and his new worldview unsettles the shared ground of ableism and anthropocentrism. Analyzing three of Lear's significant speeches, I argue that King Lear's exploration of what it means to be human anticipates Lennard Davis's recent theoretical concept, dismodernism. Both Lear and Gloucester express concern for Poor Tom in ways that link disability to community and social justice. Through considering King Lear in relation to early modern contexts and current Disability Studies theory and activism, I argue that the play is an important site for developing a socially conscious Shakespearean Disability Studies.